Patterns of homicide and robbery in Utusan Malaysia - Nik Azmah, Nik Ramly (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
This study sought to establish the patterns of homicide and robbery in Malaysia as reported in the Malay newspaper Utusan Malaysia. This study will help to identify the patterns of frequency for both violent crimes according to year, state, perpetrator demographics, and victim demographics. All necessary data was obtained and analyzed from Utusan Malaysia between the years 2004 and 2006. The results of this analysis was compared to PDRM Crime Index. Archival analysis was used in this study. The KruskalWallis Test for K Independent Samples was used to test hypotheses. There were 153 homicide cases and 74 robbery cases. The highest cases of homicide were reported in 2004 (59 cases of all cases) followed by 51 cases in 2006 and 43 cases in 2005. The most prevalent of robbery occurred in 2006 (47 cases of all cases). This was followed with 14 cases in 2004 and 13 cases in 2005. The results showed homicide and robbery victims in Malaysia were male, 'Malay' and Malaysian. The majority of homicide victims in Malaysia belonged to the age 'above 45 years old' whereas the age for robbery victims were '35.1 to 45 years old'. From the findings, male and aged '18.1 to 35 years old' were the most prevalent homicide and robbery perpetrators. The homicide and robbery in Malaysia mostly involved one victim. The highest ethnicity of murderers in Malaysia were 'Malay' after 'not stated' ethnicity. Chinese and foreigners were the most prevalent robbers in Malaysia. The comparison between Utusan Malaysia and PDRM Crime Index showed that homicide was more common as reported in Utusan Malaysia compared to robbery but the PDRM Crime Index showed robbery was more prevalent in Malaysia compared to homicide.